Mean First‐Passage Times in Biology. Issue 9 (5th August 2016) - Polizzi, Nicholas F.; Therien, Michael J.; Beratan, David N.
Abstract: Many biochemical processes, such as charge hopping or protein folding, can be described by an average timescale to reach a final state, starting from an initial state. Here, we provide a pedagogical treatment of the mean first‐passage time (MFPT) of a physical process, which depends on the number of intervening states between the initial state and the target state. Our aim in this tutorial review is to provide a clear development of the mean first‐passage time formalism and to show some of its practical utility. The MFPT treatment can provide a useful link between microscopic rates and the average timescales often probed by experiment. Abstract :